Patient satisfaction towards eye care services at tertiary eye hospitals in Madhesh Province, Nepal - Shah, Ranjan; Kumar Mishra, Sailesh; Sharma, Prakriti (Journal of Chitwan Medical College, 2024)
Background: This study aimed to assess the overall patient satisfaction with the eye care services in Madhesh Province, Nepal Method: This was a cross-sectional study conducted at eye hospitals in Madhesh province between October 2018 to January 2019. Patients who received ophthalmic care were enrolled for client exit interviews, using Likert scale tool. Data on behavior of the service provider and the services and facilities were analyzed in relation to patient satisfaction. The data were entered and analyzed using SPSS-V20. A Pearson’s chi-square test was used to examine the relationship between overall satisfaction and the dependent variables. Result: Out of 1190 patients 46(3.8%) reported visiting the hospital more than four times. The main reasons for attending hospital were the ‘quality of services’ at affordable costs 635(53.0%) followed by easy access to hospital 468(39%). Level of education, socioeconomic status, waiting time, hospital hours, cleanliness and cost of service were all significantly associated (p<0.05) with the overall patient-reported satisfaction. The behavior of the service providers did not play a statistically significant role in overall satisfaction. Conclusion: The findings indicate that 1131(95.0%) of patients reported being satisfied or highly satisfied with their overall hospital experience. This high level of patient satisfaction suggests that the hospitals are performing well in terms of perceived quality and performance. However, further analysis is recommended to identify specific areas of excellence and potential areas for improvement to ensure sustained high-quality care. Keywords: Eye Care Service, Madhesh Province, Patient’s Satisfaction, Tertiary Eye Hospital